Ultra-Fast Removal of CBB from Wastewater by Imidazolium Ionic Liquids-Modified Nano-Silica - Mengyue Zhang; Fan Yang; Nan Wang; Jifu Du; Juntao Yan; Ya Sun; Manman Zhang; Long Zhao (Molecules)
The efficient removal of dyes is of significant importance for environmental purification and human health. In this study, a novel material (Si-MPTS-IL) has been synthesized by the immobilization of imidazole ionic liquids (ILs) onto nano-silica using the radiation grafting technique. The adsorption performance of Si-MPTS-IL for Coomassie Brilliant Blue (CBB) removal is studied by a series of static adsorption experiments. It is found that Si-MPTS-IL has ultra-fast adsorption kinetics, reaching equilibrium within 2 min. The adsorption process for CBB conforms to the Langmuir model. In addition, Si-MPTS-IL exhibits a negligible impact on the adsorption efficiency of CBB with the increase in salt concentration. After six cycles of adsorption–desorption, the adsorption efficiency of Si-MPTS-IL remained above 80%, indicating excellent regenerative properties and a promising candidate for the treatment of wastewater containing CBB. A study of the mechanism indicates that the CBB capture by Si-MPTS-IL can be attributed to the synergistic effects of electrostatic interactions and pore filling.